Technologies at farmers' doorsteps - Muralidharan, K; Mathew, A C; Muralikrishna, H (Indian Horticulture, 2018)
Among the technologies identified and patent application filed, majority are in the area of prototypes of machineries/gadgets developed for specific unit operations in post-harvest processing of coconut. Three patent applications each are in the fields of plant protection and harvesting. Since the prevailing practice in the Institute was to publish all research findings in the Annual Reports, many technologies identified for commercialization failed to qualify for filing application for patents. Further, entrepreneurs also have apprehension about the volume of business that can be generated from these technologies as contribution of coconut sector to Indian agriculture is only around 1%. Thus, it is imperative that potential of commercialization of coconut technologies lies with micro, small and medium entrepreneurs. Considering these facts, three approaches were formulated to commercialize technologies, (i) handing over the rights for commercialization to other agencies such as National Research Development Corporation (NRDC); (ii) identify entrepreneurs and sign Memorandum of Agreement (MoA) with them for commercial use of specific technology; and (iii) direct selling through the Agriculture Technology Information Centre (ATIC) of the Institute.